Low-cost condition monitoring for unbalanced motor systems using tuned dynamic vibration absorber - Mohd Rosli, Mohd Affan (2025)
Unbalanced motor is referred to the situation of a rotating system where there is an uneven distribution of mass, resulting the significant vibration or imbalance problems. Poor management of unbalanced motor can lead to various issues, such as increased vibration, decreased efficiency, and potential damage of both motor and the integrated system. This study investigates the performance of reduction vibration for an integrated unbalanced motor-beam structure using a Tuned Dynamic Vibration Absorbers (TDVA), with different types of TDVA stiffness (stainless steel, aluminium, brass and titanium). To gain a better understanding of the system dynamic behavior, the natural frequencies of the beam were determined using an Experimental Modal Analysis prior to implementing the TDVA. The Operational Deflection Shapes (ODS) experiment was conducted in the z-axis direction with three different motor speeds; 880 RPM (14.8 Hz), 2100 RPM (35 Hz) and 2800 RPM (46.5 Hz) to observe the most significant vibration of the beam during operation. Later, the TDVA which consisted of two secondary masses, was employed to modify the structural dynamic response of the beam. The lengths of the TDVA masses were adjusted based on the motor speed to optimize vibration reduction of the beam. The selection of TDVA stiffness materials was driven by their varying densities, moduli of elasticity and damping capacities, providing insight into their suitability for specific operating frequencies and conditions. Various TDVA stiffness materials were applied to determine the most effective vibration attenuation and it was found that aluminium xxi material has produced the highest attenuation of 93.18 % at motor speed of 2880 RPM. Furthermore, a low-cost condition-based monitoring (CBM) system was developed using an Arduino Uno microcontroller connected to a Raspberry Pi. This system utilized an MPU9250 sensor which is cost-effective and appropriate for vibration measurement. The CBM system dashboard was hosted using the cloud, allowing real-time access to the vibration data. The system employed four programmable conditions to continuously assess the vibration activities. This affordable approach offers an accessible solution for small-scale industries, reducing reliance on expensive industrial-grade analyzers. In the event of abnormal vibration, the CBM system can trigger a notification alert, serving as a preventive measure against structure failures. The findings contribute to broader applications, including the improvement of maintenance strategies across various industries, emphasizing the transformative impact of combining effective vibration control and low-cost monitoring systems. It is also contributes to the understanding of the effect of different TDVA stiffness materials on the vibration control of beam structures with the additional of practical approach for real-time condition monitoring to improve system reliability.